Prevalence and risk factors for cancer-related fatigue in women with malignant gynecological tumors: a meta-analysis and systematic review - Jie Zhao; Liuyan Zhan; Yuanyuan Pang; Shujie Shen; Jie Huang; Wenjia Zhang; Siqi Wei (BMC Cancer)
Abstract Background Cancer-related fatigue (CRF) is one of the most prevalent symptoms, but its prevalence and associated risk factors remain inconsistent across studies. Objective To identify the prevalence and risk factors for CRF in women with malignant gynecological tumors. Methods A comprehensive search of databases, including Web of Science, Cochrane Library, PubMed, Embase, CNKI, VIP, Wan Fang, and CBM, was conducted for relevant studies published from the inception of the database until September 7, 2023. Two reviewers used EndnoteX9 software to independently review, extract data, cross-check, and use the Newcastle-Ottawa quality assessment scale and the Agency for Healthcare Research and Quality tool for risk of bias assessment to evaluate bias risk. Stata 17.0 software was used to perform a traditional meta-analysis. Results The meta-analysis included 33 studies, of which 29 reported the prevalence of CRF. The combined prevalence of CRF was 89% (95% confidence interval [CI]: 80–95%), and the combined prevalence of chronic CRF was 25% (95%CI: 22–28%). The combined prevalence of CRF in patients with ovarian cancer, cervical cancer, endometrial, and gynecological malignancies (including but not limited to cervical, ovarian, vaginal and other mixed types of gynecological cancers) was 77%, 94%, 90%, and 93%, respectively. The variability in CRF measurement is due to the different scales used across studies. Its prevalence varies by country, and developing countries, especially China, have a high prevalence of CRF. The following risk factors were associated with CRF: age (odds ratio [OR] = 1.43, 95%CI = 1.12–1.83), psychological factors (OR = 1.40, 95%CI = 1.14–1.72), disease stage (OR = 1.65, 95%CI 1.14–2.40), and social support (OR = 0.77, 95%CI 0.67–0.87). Conclusion The prevalence of CRF is significant in women with gynecological cancers, especially in developing countries. Age, psychological factors, and disease stage are risk factors for CRF, while social support serves as a protective factor. Healthcare professionals can obtain a clearer picture of CRF in women with gynecological malignant tumors and identify risk factors to support subsequent interventions in these patients. Prospero id CRD42023489433.